0=c(c+6)

Simple and best practice solution for 0=c(c+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0=c(c+6) equation:


Simplifying
0 = c(c + 6)

Reorder the terms:
0 = c(6 + c)
0 = (6 * c + c * c)
0 = (6c + c2)

Solving
0 = 6c + c2

Solving for variable 'c'.
Remove the zero:
-6c + -1c2 = 6c + c2 + -6c + -1c2

Reorder the terms:
-6c + -1c2 = 6c + -6c + c2 + -1c2

Combine like terms: 6c + -6c = 0
-6c + -1c2 = 0 + c2 + -1c2
-6c + -1c2 = c2 + -1c2

Combine like terms: c2 + -1c2 = 0
-6c + -1c2 = 0

Factor out the Greatest Common Factor (GCF), '-1c'.
-1c(6 + c) = 0

Ignore the factor -1.

Subproblem 1

Set the factor 'c' equal to zero and attempt to solve: Simplifying c = 0 Solving c = 0 Move all terms containing c to the left, all other terms to the right. Simplifying c = 0

Subproblem 2

Set the factor '(6 + c)' equal to zero and attempt to solve: Simplifying 6 + c = 0 Solving 6 + c = 0 Move all terms containing c to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + c = 0 + -6 Combine like terms: 6 + -6 = 0 0 + c = 0 + -6 c = 0 + -6 Combine like terms: 0 + -6 = -6 c = -6 Simplifying c = -6

Solution

c = {0, -6}

See similar equations:

| r^2+8r+25=0 | | -5x=-75 | | m^2+5m-2=0 | | -x^2+3=1 | | 5a-6+4a=3a+18 | | -12+32= | | 0=w(w+6) | | -7p^2-3p=-3p(p-7) | | 50=x+2x+(2x+5) | | 4b+2=3+8b | | -13y=-117 | | -3x=2(x+4) | | -x^2+3=-3x+3 | | x(x-y)-y= | | 3x+2=59 | | x^2-.6667x-2.8889=0 | | 2k-3= | | 2x+2=59 | | 0=-x^2+3 | | -130+3x=113-6x | | -3x+5=x+-5 | | -130+3x=113- 6x | | x^2-2x+6=2x^2-6x-26 | | 9x-83=3x+67 | | 12m^2-32m+20=0 | | X=-x^2+3 | | 7x+5-3x-8=8x+6+5x-9 | | X^2+17x-168=0 | | 1.4x+x=-12 | | 1.6X=6.4 | | 3(x-1)=2(2x+1)-(x+5) | | -6(x+10)=-36 |

Equations solver categories